The requirement of IRE1 and XBP1 in resolving physiological stress during Drosophila development. - Huang, H.W.; Zeng, X.; Rhim, T.; Ron, D.; Ryoo, H.D. (Journal of Cell Science, 2017)
IRE1 mediates the unfolded protein response (UPR) in part by regulating XBP1 mRNA splicing in response to endoplasmic reticulum (ER) stress. In cultured metazoan cells, IRE1 also exhibits XBP1-independent biochemical activities. IRE1 and XBP1 are developmentally essential genes in Drosophila and mammals, but the source of the physiological ER stress and the relative contributions of XBP1 activation versus other IRE1 functions to development remain unknown. Here, we employed Drosophila to address this question. Explicitly, we find that specific regions of the developing alimentary canal, fat body and the male reproductive organ are the sources of physiological stress that require Ire1 and Xbp1 for resolution. In particular, the developmental lethality associated with an Xbp1 null mutation was rescued by transgenic expression of Xbp1 in the alimentary canal. The domains of IRE1 that are involved in detecting unfolded proteins, cleaving RNAs and activating XBP1 splicing were all essential for development. The earlier onset of developmental defects in Ire1 mutant larvae compared to in Xbp1-null flies supports a developmental role for XBP1-independent IRE1 RNase activity, while challenging the importance of RNase-independent effector mechanisms of Drosophila IRE1 function.